Designing of masks for quantum dot single electron transistor fabrication using E-beam nanolithography - Uda, Hashim; Sutikno, Madnasri; Zul Azhar, Zahid Jamal (Nano Science and Technology Institute, 2009)
Link to publisher's homepage at http://www.nsti.org/procs